Subclinical Mastitis Prevalence of Dairy Goat Smallholder Farm and Total Plate Count of the Milk - Susanty, Hilda; Ratni, Eli; Sopiah, Sofa (Andalasian Livestock, 2024)
Subclinical mastitis is an inflammatory condition of the mammary gland without visible symptoms in dairy livestock. The subclinical mastitis should be detected periodically in every farm. This study aimed to determine the prevalence of subclinical mastitis in dairy goats on smallholder farms, followed by calculating the goat milk's total plate count (TPC) and pH value. Risk factors thought to cause subclinical mastitis on that farm are traditional livestock rearing techniques and land area that exceeds livestock capacity. The method used was a survey at a smallholder farm and laboratory analysis for the milk quality as a case study of a goat farm in Padang City, West Sumatra, Indonesia. The farm kept 118 goats from different breeds: Ettawa breeders, Sapera, Anglo Nubian, Anglo Sapera, and Anglo Saperaboer. Eighteen dairy goats were in the lactation period in June-July 2023. The results of subclinical mastitis examination of dairy goats were categorized as negative (-), positive 1 (+), positive 2 (++), and positive 3 (+++). The results showed that the prevalence of subclinical mastitis on that farm was 66.7%. Furthermore, milk TPC values (CFU/ml) were 3.1x105 (-), 5.6x106 (+), 9.9x106 (++), and 1.5x107 (+++). The pH values of the milk ranged from about 6.9 to 7.1. In conclusion, there was a high prevalence of subclinical mastitis on the farm. As such, the TPC and pH values were above the Indonesian National Standard for fresh milk quality.